Use GIS to Draw the concentrations Maps of the Heavy Elements and Boron of Groundwater In Southwest Karbala Governorate/Iraq - Wafur, Raad; Mustafa, Ahmed; Halub, Ibraheem (Iraqi Journal of Science, 2023)
The area of study is located at southern east of Karbala governorate, in basin of Dibdiba formation (upper Miocene-Pliocene), between longitudes (43ο 57' 34.2" & 44ο 09' 49.2ʺ) and latitudes (32ο 23' 16.4" & 32ο 36' 03.2"), this area about ( 336 ) km2. It is consists the geochemical and hydrochemical studies of heavy elements (Co, Ni, Mn, Cd, Pb, Zn, Fe) and (B+3) and measure the concentration of elements from samples of groundwater of 16 wells. After data collection from the analysis of the samples of water we are saving the results on the computer, with GIS software techniques, and draw different maps which represent the zones of the distribution of concentrations the metals. From the maps we are seen the zone of higher concentrations toward south and southeast toward the movement of groundwater(the area of discharge), and from the chemical analysis of water we can seen all water samples exceeded the limit for (B+3) and (Ni,Pb), while the other elements (Mn, Zn, Cd) within the permissible limits, while (Co)was within the permissible limits except in the well (14), and (Fe) was within the permissible limits except in the wells (13,15,16 and 20). From the results of the study we are finding that all water of the wells are contaminated because the farmers are used many kinds of fertilizers to the vegetations of the surrounding area, the chemical compositions of these fertilizers mainly composed from heavy metals, and when the farmers irrigated the farms the dissolved minerals penetrated the soils to reach the aquifer of groundwater, therefore the water of wells used just for irrigation the vegetations, and when compare the results with the Iraqi and International standers for drinking water, we can’t used all the water of the wells to human s drinks.Keywords: Fe:Iron, Ni:Nickel, Co:Cobalt, Pb:Lead, Cd:Cadimium